Answer :
Going from y=x^2 -> y= (x+9)^2 -3 involves two steps.
#1. Compare y1= x^2 to y2 = (x+9)^
X | y1 | y2
0 | 0 | 81
1 | 1 | 100
They both have the same function structure, but the y2 is shifted 9 units to the left.
#2 from y= x^2 -> y= x^2 -3 simply involves shifting the function downward by 3 units.
So, to transform y = x^2 -> y = (x+9)^2 -3, you must shift the function left by 9 units and shift it down by 3
#1. Compare y1= x^2 to y2 = (x+9)^
X | y1 | y2
0 | 0 | 81
1 | 1 | 100
They both have the same function structure, but the y2 is shifted 9 units to the left.
#2 from y= x^2 -> y= x^2 -3 simply involves shifting the function downward by 3 units.
So, to transform y = x^2 -> y = (x+9)^2 -3, you must shift the function left by 9 units and shift it down by 3